THE ROLE OF ISLAMIC PHILANTHROPY IN POVERTY ALLEVIATION: A SYSTEMATIC LITERATURE REVIEW OF CONCEPTS, MECHANISM, AND PRACTICAL CHALLENGES - Dita Herdian (PT. Samudra Solusi Profesional, 2025)
poverty remains a persistent socio-economic challenge in many Muslim-majority countries and beyond. Islamic philanthropy through instruments such as zakat, infaq, sadaqah, and waqf is often proposed as a faith-based mechanism for redistributing wealth and reducing poverty. This article presents a systematic literature review of empirical and theoretical research on Islamic philanthropy’s contributions to poverty alleviation. Following PRISMA guidelines for qualitative synthesis, the study examines peer-reviewed journal articles, institutional reports, and documented case studies to identify both conceptual insights and practical trends in the field. The review reveals that zakat functions as an obligatory redistributive tool that supports income redistribution and social equity, while waqf and other voluntary philanthropic instruments complement this by providing long-term resources for healthcare, education, and microenterprise development. Research from West Java, Nigeria, Pakistan, and Indonesia shows that Islamic philanthropic funds can enhance welfare outcomes for poor and vulnerable populations when effectively managed and transparently administered. However, findings also indicate significant institutional challenges, such as inadequate governance frameworks, low literacy among potential donors and recipients, and technological barriers that limit outreach and impact measurement. Digital innovation emerges in the literature as a promising strategy to enhance collection efficiency, transparency, and beneficiary targeting. Moreover, Islamic philanthropy’s alignment with Sustainable Development Goals (SDGs) suggests its broader relevance not only for Muslim societies but for comparative social finance research globally. Despite evidence of positive philanthropic impacts, gaps remain in longitudinal impact evaluations and multi-country comparative studies. The synthesis concludes with recommendations for strengthening institutional capacity, fostering cross-sector partnerships, and improving monitoring and evaluation systems to maximize the poverty alleviation potential of Islamic philanthropic instruments.